SHANK2 mutations impair apoptosis, proliferation and neurite outgrowth during early neuronal differentiation in SH-SY5Y cells - Unsicker, Christine; Cristian, Flavia-Bianca; Hahn, Manja von; Eckstein, Volker; Rappold, Gudrun; Berkel, Simone (Scientific reports, 2021)
SHANK2 mutations have been identified in individuals with neurodevelopmental disorders, including intellectual disability and autism spectrum disorders (ASD). Using CRISPR/Cas9 genome editing, we obtained SH-SY5Y cell lines with frameshift mutations on one or both SHANK2 alleles. We investigated the effects of the different SHANK2 mutations on cell morphology, cell proliferation and differentiation potential during early neuronal differentiation. All mutant cell lines showed impaired neuronal differentiation marker expression. Cells with bi-allelic SHANK2 mutations revealed diminished apoptosis and increased proliferation, as well as decreased neurite outgrowth during early neuronal differentiation. Bi-allelic SHANK2 mutations resulted in an increase in p-AKT levels, suggesting that SHANK2 mutations impair downstream signaling of tyrosine kinase receptors. Additionally, cells with bi-allelic SHANK2 mutations had lower amyloid precursor protein (APP) expression compared to controls, suggesting a molecular link between SHANK2 and APP. Together, we can show that frameshift mutations on one or both SHANK2 alleles lead to an alteration of neuronal differentiation in SH-SY5Y cells, characterized by changes in cell growth and pre- and postsynaptic protein expression. We also provide first evidence that downstream signaling of tyrosine kinase receptors and amyloid precursor protein expression are affected.
Gesehen am 25.03.2021